A Broad Range of Chemokine Receptors Are Used by Primary Isolates of Human Immunodeficiency Virus Type 2 as Coreceptors with CD4 - McKnight, Áine (American Society for Microbiology, 1998)
Like human immunodeficiency virus type 1 (HIV-1) and simian immunodeficiency virus (SIV), HIV-2 requires a coreceptor in addition to CD4 for entry into cells. HIV and SIV coreceptor molecules belong to a family of seven-transmembrane-domain G-protein-coupled receptors. Here we show that primary HIV-2 isolates can use a broad range of coreceptor molecules, including CCR1, CCR2b, CCR3, CCR4, CCR5, and CXCR4. Despite broad coreceptor use, the chemokine ligand SDF-1 substantially blocked HIV-2 infectivity of peripheral blood mononuclear cells, indicating that its receptor, CXCR4, was the predominant coreceptor for infection of these cells. However, expression of CXCR4 together with CD4 on some cell types did not confer susceptibility to infection by all CXCR4-using virus isolates. These data therefore indicate that another factor(s) influences the ability of HIV-2 to replicate in human cell types that express the appropriate receptors for virus entry.